Computed tomography-guided anterior approach to the superior hypogastric plexus for noncancer pelvic pain: a report of two cases - Michálek, Pavel; Dutka, Juraj (The Clinical journal of pain, 2005)
The objective of this study was to evaluate the possibility and describe the methodology of a computed tomography-guided anterior approach to superior hypogastric plexus block for noncancer pain. A computed tomography-guided anterior approach to the superior hypogastric plexus was used in 2 patients with pelvic pain and anatomic disturbance of the lumbar spine, which was a contraindication to the conventional dorsal approach. The first case was a 43-year-old patient suffering from burning pain of the urethra. Pain relief using analgesics and antidepressants was insufficient. The posterior approach was excluded due to coexisting irritation of the L5 nerve root. The second case was a 68-year-old man suffering from chronic burning and itching pain of the urethra and glans penis. Conservative therapy (anti-inflammatory drugs, tramadol, spasmolytics) failed to provide satisfactory pain relief. The posterior approach was contraindicated because of laterally prominent L5 vertebral body osteophytes. Both patients received a prognostic block to the superior hypogastric plexus via the anterior approach guided by computed tomography. Visual analog scale scores prior to the block were 6 to 7 and 5 to 6, respectively. The visual analog scale scores 24 hours after the block were 1 and 0, respectively. The second patient received a permanent neurolytic block via the anterior approach to provide long-term pain relief. In conclusion, the authors describe the computed tomography-guided anterior approach to the superior hypogastric plexus for chronic pelvic pain. The technique is simple to perform, and the analgesic effect is satisfactory. More extensive studies are necessary to evaluate the safety of this approach.
Keywords: ženské pohlaví; Female; Image Processing, Computer-Assisted; Humans; lidé; Aged; dospělí; Hypogastric Plexus; Pelvic Pain; plexus hypogastricus; počítačová rentgenová tomografie; počítačové zpracování obrazu; Adult; Tomography, X-Ray Computed; senioři; Male; mužské pohlaví; pánevní bolest